Etiological Characteristics and Treatment Outcomes of Eye Lid Laceration: A Hospital Based Prospective Study - Thapa, Bikram Bahadur; Gurung, Nanda Kumari (Journal of Nepalgunj Medical College, 2022)
Introduction: Lid laceration is a very common peri-ocular trauma. Regarding the etiology and treatment, it lacks studies in developing nations including Nepal. Aims: To assess the etiological characteristics and treatment outcomes of eyelid laceration. Methods: In this study, 47 cases of traumatic eyelid laceration were consecutively studied and its epidemiology, etiology and treatment outcome were evaluated. Results: The 47 patients were included in the study. The mean age of study population was 26.14 ± 18.02 years. Male: female ratio was 1.6:1. The trauma occurred on road in 34 (72.3%) cases, followed by at home (14.9%), at work place (8.5%) and at entertainment areas (4.2%). The most common mode of injury was road traffic accident (72.3%) followed by fall injury (17%), Physical assault (6.4%) and animal bite (4.3%). The 68.1% of had isolated lid laceration, 12.7% had other adnexal injuries and 10.6% had globe injuries, 8.5% had other facial injuries and only 4.1% had systemic trauma. The partial thickness laceration was observed on 42(89.4%) cases and full thickness laceration on 5 (10.6%) cases. The length of lid laceration ranged from 4- 45 mm (mean ±SD was 14.7±8.3 mm). The 14.9% cases had canalicular laceration. The 85% of the laceration healed without visible scar. Only 4 patients (8.5%) had thick hypertrophic scar. The visual function was intact in 44 patients whereas impaired in 3 patients with accompanying open globe injury. The complications noted were hypertrophic scar (8.6%), wound infection (2.1%), ectropion (2.1%), corneal opacity (2.1%) and phthisis bulbi (2.1%). Conclusion: This study highlights the high-risk people and work place for eyelid laceration and the safety precautions in dangerous settings, including daily and routine work places. Only accompanying open globe injury can damage visual function.